2012
DOI: 10.1021/jz301689b
|View full text |Cite
|
Sign up to set email alerts
|

Iron Binding Site in a Global Regulator in Bacteria–Ferric Uptake Regulator (Fur) Protein: Structure, Mössbauer Properties, and Functional Implication

Abstract: Fur protein plays key roles in regulating numerous genes in bacteria and is essential for intracellular iron concentration regulation. However, atomic level pictures of the iron binding site and its functional mechanism remain to be established. Here we present results of the first quantum chemical investigation of various first- and second-shell models and experimental Mössbauer data of E. Coli Fur, including 1) the first robust evidence that site 2 is the Fe binding site with a 3His/2Glu ligand set, being th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…Moreover, all of the residues involved in metal ion binding are conserved across Fur proteins from different species. In agreement with the previously reported Mössbauer data of E. coli Fur, site 1 is the Fe 2+ -binding site with a 3His/2Glu ligand set 36 . Another study 13 indicated that E. coli Fur has a similar affinity for Mn 2+ and Fe 2+ .…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, all of the residues involved in metal ion binding are conserved across Fur proteins from different species. In agreement with the previously reported Mössbauer data of E. coli Fur, site 1 is the Fe 2+ -binding site with a 3His/2Glu ligand set 36 . Another study 13 indicated that E. coli Fur has a similar affinity for Mn 2+ and Fe 2+ .…”
Section: Discussionsupporting
confidence: 91%
“…The only reported structures have a Zn 2+ ion in place of the regulatory metal912 and with its d 10 electronic structure Zn 2+ is insensitive to ligand field and thus cannot reveal subtle changes in the coordination sphere of the regulatory metal. To understand this structural change at the molecular level we used a combination of Mössbauer spectroscopy and density functional theory (DFT) calculations, which have recently been used in concert to derive spectroscopically validated structural properties 1316. To get insights into the coordination changes brought about by the Asp/Glu substitutions, we decided to study PerR and Fur variants possessing the three carboxylate combinations Asp/Asp, Asp/Glu, and Glu/Glu in the 85 and 104 positions (with Bs PerR numbering).…”
Section: Oxidation and Mössbauer Quadrupole Splittings Of Bs Perr Andmentioning
confidence: 99%
“…HpFur, for example, has three metal-binding sites, referred to as S1, S2, and S3 (38). Nearly all of the residues involved in metal binding are conserved in the Fur-like proteins of Thermus (39,40).…”
Section: Resultsmentioning
confidence: 99%